1998
DOI: 10.1097/00004836-199810000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Reactions Associated With Famotidine

Abstract: H2-receptor antagonists may cause various types of central nervous system reactions, particularly in patients with advanced age and/or impaired renal or liver function. These reactions have rarely been reported in association with famotidine. In five elderly patients, four of them with renal failure, central nervous system reactions developed shortly after initiation with famotidine therapy. These adverse reactions completely resolved after famotidine withdrawal. The authors' five cases and the other seven pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Failure to reduce doses of famotidine in patients with severe renal impairment is known to be associated with mental status changes including confusion, agitation, delirium, irritability, and hallucinations. 27,28 Our results are consistent with several retrospective studies in more than 20,000 patients with CKD reporting that use of the MDRD equation overestimates Cl cr , leading to significantly higher drug doses compared with doses calculated by using CG. [29][30][31][32] Our median discordance of 28% for the MDRD equation is consistent with data reported in one study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Failure to reduce doses of famotidine in patients with severe renal impairment is known to be associated with mental status changes including confusion, agitation, delirium, irritability, and hallucinations. 27,28 Our results are consistent with several retrospective studies in more than 20,000 patients with CKD reporting that use of the MDRD equation overestimates Cl cr , leading to significantly higher drug doses compared with doses calculated by using CG. [29][30][31][32] Our median discordance of 28% for the MDRD equation is consistent with data reported in one study.…”
Section: Discussionsupporting
confidence: 89%
“…For example, use of the MDRD equation resulted in a 41% discordance rate for famotidine, in which all discordant cases would have resulted in higher doses being given to patients if the MDRD equation was used instead of the CG equation. Failure to reduce doses of famotidine in patients with severe renal impairment is known to be associated with mental status changes including confusion, agitation, delirium, irritability, and hallucinations …”
Section: Discussionmentioning
confidence: 99%
“…The Odeh's work [11] also evidenced the role of age and underlying renal failure in the occurrence of central ADRs (but not mania) with famotidine. They can also suggest some predisposing factors for manic episodes associated with H2 receptor antagonists: age (most of cases occurred in old patients), decrease in renal and/ or hepatic function, or polymedication, sometimes but not always.…”
Section: Discussionmentioning
confidence: 98%
“…Many medications are widely prescribed for these indications in both the general population and in patients with kidney disease. Care should be taken with use of these agents in patients with ESRD because of inherent characteristics of the drugs and dialysis 5–10 . Despite the high prevalence of indications for GI medications in the dialysis population, relatively little is known about proton pump inhibitor (PPI) and H 2 receptor antagonist (HA) prescription patterns, apart from frequency of use.…”
Section: Introductionmentioning
confidence: 99%
“…Care should be taken with use of these agents in patients with ESRD because of inherent characteristics of the drugs and dialysis. [5][6][7][8][9][10] Despite the high prevalence of indications for GI medications in the dialysis population, relatively little is known about proton pump inhibitor (PPI) and H 2 receptor antagonist (HA) prescription patterns, apart from frequency of use. The 1998 annual report from the United States Renal Data System (USRDS), which described data collected in 1996, showed that 30% of patients sampled were prescribed either agent, but did not specify the exact proportions of the agents used.…”
Section: Introductionmentioning
confidence: 99%